Stereotypical Views of Private Sector Employees about Public Sector Employees' Performance in Kingdom of Bahrain - Amira Karam Eldin (European Scientific Journal, ESJ, 2016)
The researcher observed a widely-held stereotype about the performance of the public-sector employees in general society discourse, and especially with private-sector employees. Public-sector employees are taken as individuals who settle at mediocre performance. This research aims to test these observations using hypothesis analysis. One questionnaire was distributed on a sample of private sector employees to survey their perceptions about public sector employees' performance. Another questionnaire was distributed on a sample of public sector employees to find whether they are aware of these stereotypical views, and whether this awareness causes frustration emotions. H1: private-sector employees have negative stereotypical views about public-sector employees’ performance H2: public sector employees know about the negative stereotypes held by private-sector employees about their performance H3: public sector employees experience emotions of frustration by the negative stereotypes held by private-sector employees about their performance Two self-administered questionnaires were designed, one for the private sector employees to survey their perceptions about the public sector employees' performance, and the other one for public sector employees to survey whether they are aware about these stereotypes, and whether this awareness produces emotions of frustration. The questionnaires included demographic questions, close-ended questions and one open question for remarks. The Likert scale was used for close-ended questions to seek the respondents' opinions on a list of statements. The results validated all hypotheses. Nonetheless, we found that the stereotypes are not deeply embedded. In essence, we argue that they represent a manifestation of customer dissatisfaction gained from private sector employees' experiences with public sector front offices. These findings highlight the importance of maintaining high level front-office services at the public sector as the disappointments are generalized to the organizations in whole and all their employees.